Rencana Strategi Bersaing Dan Pemasaran Dengan Metode K-Means Cluster, Multidimensional Scaling, Dan Cross Classified Frequency - Budiono, B (Department Industrial Engineering, University of Muhammadiyah Malang, 2003)
Marketing represent method which used by a lot of side in development or extehsion of market compaxtnent.By defenitif Marketing is an sqcial process and manajerial making individual and group. obtaining what they require and wish, through reciprocal transfer and creation of product and value others. lndustrial engineedng of muhammadiyah malang university as an institution under shade of Private sector College that is university of muhammadiyah malang. of cours€ very pay aftention to marketing problem. because it caanot deni€d that marketing playing a part important in student improvement in amount. With data existence that is degradation tendency sum up student, of cowse required an effective marketing system to utilize the improvcment of sum up student. K_Means Cluster, Multidimensional Scaling and Cross Classified Frequency rcpresenting some of appliance of analysis used in determination of market segment of Induslrial engineering, by K_Means [is] Cluster, position of industrial engineering UMM compared to competitor with Multidimensional Scaling and also Cross Classified Frequency ( crosstab ) analysis which used in behavioral determination of Industrial engineering consumer of I-IMM. Applying frorn analysis expected to bring positive impact to marketing formulation of industrial engineering of UMM, that is marketing more emphasized at segment of certain ma.ket with paid attention to segment of analysis resul! for tlle competitor, hence the marketing more emphasized at competitor according to analyse result and for crosstab, marketing €mphasized at a consumer behavior in chosening Industrial engineering of UMM, that is by tipologi consumer behavior. so that th€re is imFovement quantitatively sum up Industrial engineering student of tMM after analysis conducted.